Beban Kerja dan Lama Kerja Dengan Kepatuhan Petugas Puskesmas Dalam Implementasi SOP (Standar Operasiaonal Prosedur) - Daniel Ginting; Nina Fentiana (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Standard Operating Procedures (SOP) are a series of standardized written instructions regarding various processes for carrying out organizational activities, how and when they must be carried out, where and by whom they are carried out. Community health center officers must comply with applicable SOPs in providing services to the community in order to improve the highest level of public health. The research used a cross-sectional design at the UPTD Awa'ai Health Center, North Nias Regency with a sample size of 61 respondents. Data analysis uses the Chi Square test. The research results show that there is a relationship between workload and length of work with compliance with implementing service SOPs (P-Value <0.005)